Ruang Lingkup Manajemen Pendidikan - Achmad Wahyudin; Anis Zohriah (Journal on Education, 2023)
As a conscious and planned effort, education is an effort to develop the potential of students to have religious spiritual strength, self-control, personality, intelligence, character, and skills needed by themselves, society, nation and state. To realize efforts to achieve educational goals, educational institutions need a measurable and planned regulatory pattern. So educational institutions need good institutional management. In education management must focus on the object of study, so that human resources, funding, materials, methods, markets and time can be managed properly. Likewise, the field of work on education management must be given serious attention so that students, curriculum, personnel, education financing, and community relations can be properly managed through quality management of educational institutions.